Value-at-risk in the presence of asset price bubbles - Raymond Kwong; Helen Wong (Journal of Applied Economics, 2022)
In this study, we respond to the criticism that the value-at-risk (VaR) measure fails during financial crises and is only applicable during periods without asset price bubbles. We propose a new dating mechanism that is based on the work of Phillips (2015) to date-stamp the origination and termination of the asset price bubbles. Our method relaxed the minimum bubble duration constraint in the original model, and the empirical application statistically identified the bubbles periods in nine stock markets (Australia, Canada, China, Germany, Spain, Hong Kong, Japan, the United Kingdom, and the United States). We choose the two most widely adopted VaR models (RiskMetrics and RiskMetrics 2006) to test the performance. Our results show that the RiskMetrics model fails in most periods, whereas the RiskMetrics 2006 performs efficiently in the periods with asset price bubbles. These results prove the criticism that all the VaR models fail during crises as invalid.
Keywords: 330; Asset price bubbles; date-stamping bubbles; financial crisis; value-at-risk